Evaluation of oxidation and adsorption techniques for taste and odor and toxin removal - Sampath, Muthukumaran, author; Omur-Ozbek, Pinar, advisor; Carlson, Kenneth, committee member; Dooley, Gregory, committee member (Colorado State University. Libraries, 2017)
The cyanobacteria, also known as blue-green algae, owe their name to the presence of photosynthetic pigments. Cyanobacteria are a major group of bacteria that occur throughout the world. Freshwater cyanobacteria may accumulate in surface water supplies as "blooms" posing as an environmental hazard because of the release of water soluble toxic compounds, called cyanotoxins. Especially massive blooms of blue–green algae in the surface waters used as drinking water resources may lead to taste and odor problems during the summer and fall, they may also produce cyanotoxins. Since the taste and odor compounds, Geosmin (GSM) and 2-Methylisoborneol (2-MIB) can be easily detected by the human nose at low concentrations of 2-5 ng/L, the surveillance of harmful toxins such as microcystin-LR may be easily performed by sensory analyses due to the likely co-occurrences of the two types of metabolites. This research focused on removal of taste and odor compounds (GSM, 2-MIB) and microcystin-LR with five oxidants: chlorine, chlorine dioxide, potassium permanganate, ozone, mixed oxidants (MiOX) and powdered activated carbon (PAC) using Ralston Reservoir water as reagent water collected in early April, 2014. The objective of the study was to develop a bench scale treatment process efficacy information that Denver Water can utilize to decide on a treatment technique for taste and odor control. The Design Expert software was used to determine the optimum dose of the oxidants for an acceptable treatment level.
Keywords: odor; taste; algae; toxin; removal